2015
DOI: 10.1371/journal.pone.0124985
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible Transmembrane Protein 3 Genetic Variant rs12252 and Influenza Susceptibility and Severity: A Meta-Analysis

Abstract: BackgroundThe pandemic influenza A (H1N1) pdm09 virus, avian influenza A (H5N1) virus, and influenza A (H7N9) virus induced severe morbidity and mortality throughout the world. Previous studies suggested a close association between the interferon-induced transmembrane protein-3 (IFITM3) genetic variant rs12252 and influenza. Here, we explored the correlation between the rs12252 and influenza susceptibility and severity using meta-analysis.MethodsRelevant studies published before May 22, 2014 were retrieved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Individuals homozyogous for the IFITM3 allele, rs12252-C, are at increased risk of severe influenza (Everitt et al, 2012;Yang et al, 2015;Zhang et al, 2013). While rare in individuals of European ancestry, the rs12252-C allele is more prevalent in Asia and Micronesia.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals homozyogous for the IFITM3 allele, rs12252-C, are at increased risk of severe influenza (Everitt et al, 2012;Yang et al, 2015;Zhang et al, 2013). While rare in individuals of European ancestry, the rs12252-C allele is more prevalent in Asia and Micronesia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of IFITM3 in animal studies and in vitro models 5,6 , several groups investigated polymorphisms in IFITM3 for associations with disease outcome. The C/C genotype of rs12252 in IFITM3 was linked to severe illness in adults during the 2009 IAV pandemic 79 , but the mechanism for this risk allele remains unresolved. The rs12252 C allele correlation with influenza severity has been validated in two cohorts of Han Chinese, where the majority carry at least one C allele 7,10 , but not in cohorts of European ancestry 1113 , suggesting that the effects of this allele may vary across ancestral populations.…”
mentioning
confidence: 99%
“…Moreover, the CC genotype was found in 25% of Chinese patients showing mild disease after pH1N1 virus infection compared to 69% in patients developing a severe pH1N1 virus infection. In addition, the CC genotype was estimated to confer a six-fold increased risk for severe infection than the CT and TT genotypes [120], reinforcing the idea that IFITM3 is a factor affecting human IAV disease [121]. In another study, over-representation of the IFITM3 CC genotype was detected among fatal cases of Chinese patients infected with IAV pH1N1 and H7N9 viruses [100], and in a more general study, including twelve studies published before February 2018 with more than 16,000 subjects, revealed increased risk of severe influenza in both the East Asian and White populations in the subjects encoding the IFITM3 CC genotype [122].…”
Section: Snps In Host Genes Affecting Iav Diseasementioning
confidence: 75%